KERAJINAN TALI KUR SEBAGAI UPAYA PENINGKATAN EKONOMI KELUARGA KELOMPOK DASA WISMA DI DESA MANUNGGAL KECAMATAN LABUHAN DELI KAB. DELI SERDANG - Rini Ekayati; Imelda Darmayanti Manurung (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Out of the 15 hamlets in Desa Manunggal, Kec. Lab. Deli, Kab. Deli Serdang is only one hamlet that owns the Dasa Wisma group, namely VII A Hamlet with the name Dasa Wisma Matahari Group. The Dasa Wisma group in VII A Hamlet consists of 10 (ten) groups, starting from the Matahari Group I - X. The number of members in each group is 10 (ten) people, so the total number of members is 100 (one hundred) members. This is a resource that can be empowered to help improve the family economy. However, currently the existing Dasa Wisma group does not have activities to increase the skills capacity of its group members. So, there needs to be an effort to design activities that can overcome these problems through community partnership programs (PKM). The lack of knowledge and skills in utilizing rope kur into bag products with various motifs is the main problem of concern of the program. Therefore, the solution offered is to hold a workshop (training) on rope kur crafts to increase the skills of the dasa wisma group members so that they can become the capital of opening new businesses. At the end of the program, the results obtained were the implementation of training activities for crafting rope kur into bags of various economic-value motifs.